2022
DOI: 10.1111/2047-3095.12362
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ perceptions of nursing diagnoses, critical thinking motivations, and problem‐solving skills during distance learning: A multicentral study

Abstract: To determine the relationship between attitude towards nursing diagnosis, critical thinking motivation, and problem-solving skills of nursing students during distance learning. Method:The descriptive and correlational study was conducted with 450 first-year nursing students from four universities. The "Positions on Nursing Diagnosis Scale," "Critical Thinking Motivational Scale," and "Problem Solving Inventory" were used for data collection in June-July 2021. Findings:The students' mean score of nursing diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
2
7
0
3
Order By: Relevance
“…Mirzaei et al reported that teaching life skills enhances adaptive strategies such as positive refocusing, and individuals act positively in consciously regulating their emotions and become more proficient in applying adaptive strategies such as positive refocusing (Mirzei and Hasani, 2015 ). Catastrophizing was negatively correlated with problem-solving skills among the EMS staff, which was consistent with the results of previous studies (Mirzei and Hasani, 2015 ; Nasrolahi and Pour, 2018 ; Bayram et al, 2022 ). The results of these studies show that increasing life skills reduces adaptive strategies such as catastrophizing.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Mirzaei et al reported that teaching life skills enhances adaptive strategies such as positive refocusing, and individuals act positively in consciously regulating their emotions and become more proficient in applying adaptive strategies such as positive refocusing (Mirzei and Hasani, 2015 ). Catastrophizing was negatively correlated with problem-solving skills among the EMS staff, which was consistent with the results of previous studies (Mirzei and Hasani, 2015 ; Nasrolahi and Pour, 2018 ; Bayram et al, 2022 ). The results of these studies show that increasing life skills reduces adaptive strategies such as catastrophizing.…”
Section: Discussionsupporting
confidence: 92%
“…Given the positive association between cognitive emotion regulation and increased self-confidence as well as the emergence of better social behaviors, it is not surprising that this multidimensional structure- adaptive or maladaptive emotion regulation strategies-affects cognitive problem-solving skills embedded in decision-making and critical thinking ability (Aminabadi et al, 2011 ; Te Brinke et al, 2018 ). Problem-solving skills include a combination of behavioral, cognitive, and emotional reactions that manifest when a person encounters everyday problems to adapt to intrinsic actions and overcome the pressures arising from them (Ancel, 2016 ; Bayram et al, 2022 ). Accordingly, they try to search for various sources and then apply useful strategies (Huang and Flores, 2011 ; Tan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most nursing students are educated to follow the PES format for problem-focused or health-promotion diagnosis when stating a nursing diagnosis ( Burucu and Arslan, 2021 ; Florin et al, 2005 ). Problems refer to the response of the patients, etiology refers to the related or risk factor that causes nursing problems, and signs or symptoms are specific responses that occur in a patient, supporting that the cause is related to the nursing problem ( Bayram et al, 2022 ; Karaca and Aslan, 2018 ; Ozkan et al, 2021 ). For example, with the statement “impaired physical mobility related to activity intolerance,” it is difficult to clearly ascertain the evidence for making the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the nursing process is an important indicator covering a high proportion of guidance and evaluation areas in clinical practice education, it is reported that nursing students still have difficulties in the clinical application of this process. In other words, the significance of the nursing process in clinical practice has been emphasized, but specific efforts for improvement remain insufficient ( Bayram et al, 2022 ; Keiffer, 2018 ; Melin-Johansson et al, 2017 ; Parvan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%